2014
DOI: 10.1016/j.econmod.2013.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Does employment protection legislation affect firm investment? The European case

Abstract: This paper aims at analyzing the impact of Employment Protection Legislation (EPL) on firm's investment policy in the presence of financial imperfections. Our results show a negative correlation between EPL levels and investments. Firms facing negative shocks see their financial constraints worsening in countries with greater labour market rigidities. The presence of stricter EPL disincentives the use of internal funds for financing new projects: i.e., if capital is largely sunk and the legal environment favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Cingano et al (2014) use a large Italian firm-level dataset (of more than 25,000 observations) and show that the implementation, in 1990, of a reform that introduced unfair-dismissal costs for firms below 15 employees had increased in these firms the capital-to-labour ratio, particularly in labour-intensive firms. But in a previous study carried out using a large panel of European firms, Cingano et al (2010) had found a negative impact of EPL on the capital-to-labour ratio, and Calcagnini et al (2014) also found a negative empirical relation between EPL and investment dynamics using a small European firm-level dataset (2,600 firms in 10 European countries). For Cingano et al (2014), these differences in the results of their two studies "may be reconciled by adopting the view, proposed by Janiak and Wasmer (2014)".…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…Cingano et al (2014) use a large Italian firm-level dataset (of more than 25,000 observations) and show that the implementation, in 1990, of a reform that introduced unfair-dismissal costs for firms below 15 employees had increased in these firms the capital-to-labour ratio, particularly in labour-intensive firms. But in a previous study carried out using a large panel of European firms, Cingano et al (2010) had found a negative impact of EPL on the capital-to-labour ratio, and Calcagnini et al (2014) also found a negative empirical relation between EPL and investment dynamics using a small European firm-level dataset (2,600 firms in 10 European countries). For Cingano et al (2014), these differences in the results of their two studies "may be reconciled by adopting the view, proposed by Janiak and Wasmer (2014)".…”
Section: Literature Reviewmentioning
confidence: 90%
“…1 Autor et al (2007) show that the adoption of wrongful-discharge protection by state courts in the US from 1970 to 1999 increased the capital-to-labour ratio and Cingano et al (2014) show that the implementation in Italy in 1990 of a reform that introduced unjust-dismissal costs for firms below 15 employees had increased in these firms the capital-to-labour ratio. But using a panel of European firms, Cingano et al (2010) and Calcagnini et al (2014) had found a negative impact of EPL on the capital-to-labour ratio and on investment dynamics respectively. These results may be reconciled by idea of Janiak and Wasmer (2014) of an inverted U-shape relationship between the employment protection legislation and the capital-to-labour ratio: at a low (high) EPL level, a positive (negative) correlation appears between EPL and capital intensity.…”
Section: Introductionmentioning
confidence: 98%
“…As described at the beginning of this Section, it is assumed that product, labor market and financial market imperfections affect firms' profitability, and through it investment, while financial market imperfections also influence investment directly. Differently from previous empirical works that assumed a direct impact of product Alesina (2005) or labour Calcagnini (2013) market regulation on firm investment, the hypothesis is that product and labour market imperfections affect firm investment decisions indirectly, through their impact on firm profitability Griffith et al (2007). Said differently, this approach assumes that such regulations affect firm investment only through their impact on competition and input costs, and the statistical validity of these exclusion restrictions is tested.…”
Section: Market Regulations and Firm Investmentmentioning
confidence: 95%
“…Indeed, in the presence of financial constraints, investment becomes sensitive to the availability of internal sources of finance. The liquidity variable used is total cash-in-hand available to the firm, (LIQ), instead of the cashflow variable, that might not efficiently measure the extent to which investment depends on internally generated funds (Calcagnini et al 2009(Calcagnini et al ,2013. 16 Fourth, the impact of financial development (FMD) of a country is controlled by means of, alternatively, the three measures described above, i.e.…”
Section: Market Regulations and Firm Investmentmentioning
confidence: 99%
See 1 more Smart Citation